Characterization of Transverse Aortic Constriction in Mice Based on the Specific Recruitment of Leukocytes to the Hypertrophic Myocardium and the Aorta Ascendens - Jan Lukas Kleiner; Odilia Köpke; Anton Faron; Yunyang Zhang; Jan Cornelssen; Mark Coburn; Stilla Frede; Lars Eichhorn; Christina Katharina Weisheit (Mediators of Inflammation)
Transverse aortic constriction (TAC) is a model that mimics pressure overload-induced left ventricular (LV) hypertrophy in mice. Alterations in immune cell functionality can promote cardiac and vascular remodeling. In the present study, we characterized the time course in innate immune cell dynamics in response to TAC in the different tissues of mice. It was determined whether TAC induces a characteristic leukocyte-driven immune response in the myocardium, aorta ascendens and descendens, spleen, blood, and draining lymph nodes supported by cytokine-driven chemotaxis in mice at 3, 6, and 21 days following surgery. We used complex flow cytometry staining combinations to characterize the various innate immune cell subsets and a multiplex array to determine cytokine concentrations in the serum. The results of the current study indicated that leukocytes accumulate in the myocardium and aorta ascendens in response to TAC. The leukocyte dynamics in the myocardium were dominated by the Ly6Clow macrophages with an early accumulation, whereas the response in the aorta ascendens was characterized by a long-lasting proinflammatory phenotype driven by Ly6Chigh macrophages, neutrophils, and activated DCs. In contrast to the high-pressure environment of the aorta ascendens, the tissue of the aorta descendens did not react to TAC with any leukocyte increase. The levels of proinflammatory cytokines in the blood were elevated in response to TAC, indicating a systemic reaction. Moreover, our findings strongly suggest that cardiac macrophages could origin from splenic pools and reach the site of the inflammation via the blood. Based on the current findings, it can be concluded that the high-pressure conditions in the aorta ascendens cause a characteristic immune response, dominated by the accumulation of leukocytes and the activation of DCs that varies in comparison to the immune cell dynamics in the myocardium and the aorta descendens.